2020
DOI: 10.3390/e23010048
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Chaos Complexity of a Plasma Model through Power Input with Desirable Random Features

Abstract: The present work introduces an analysis framework to comprehend the dynamics of a 3D plasma model, which has been proposed to describe the pellet injection in tokamaks. The analysis of the system reveals the existence of a complex transition from transient chaos to steady periodic behavior. Additionally, without adding any kind of forcing term or controllers, we demonstrate that the system can be changed to become a multi-stable model by injecting more power input. In this regard, we observe that increasing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Yang and Chien [16] examined the success of the hardware realization of chaotic systems for the four-dimensional chaotic system and combined the obtained outputs with AES in an image encryption algorithm. Natiq et al [17] proposed a random number generator based on the chaotic behavior of the plasma model. Özkaynak [18] has shown that, by using the fractional order model of the chaotic Chen system, the randomness requirements can be improved, and this can be a positive effect for cryptographic purposes.…”
Section: Related Workmentioning
confidence: 99%
“…Yang and Chien [16] examined the success of the hardware realization of chaotic systems for the four-dimensional chaotic system and combined the obtained outputs with AES in an image encryption algorithm. Natiq et al [17] proposed a random number generator based on the chaotic behavior of the plasma model. Özkaynak [18] has shown that, by using the fractional order model of the chaotic Chen system, the randomness requirements can be improved, and this can be a positive effect for cryptographic purposes.…”
Section: Related Workmentioning
confidence: 99%
“…Because entropy issues in novel chaotic systems are important in the theoretical development of this research study, it is worth mentioning some articles found in the literature on the entropy of novel chaotic systems. As an example, in papers such as that in [ 67 ], the enhancing of chaos complexity of a plasma model is demonstrated. It is demonstrated in this paper that by increasing the power input, the system can change from monostable to multistable without the addition of any input terms.…”
Section: Related Workmentioning
confidence: 99%
“…Some chaotic dynamics with different types of symmetries have been introduced [29]. Among features related to the topology of attractors, ones which have multiscrolls are interesting for researchers [30]. Assessing the stability of multiscrolls attractors [31] and finding methods to preserve multiscrolls [32] are topics that grab much attention.…”
Section: Introductionmentioning
confidence: 99%